A strategy design based on antibiotic‑resistance and plasmid replicons genes of clinical Escherichia coli strains. Issue 3 (1st March 2022) - Liu, Junyan; Lin, Xin; Soteyome, Thanapop; Ye, Yanrui; Chen, Dingqiang; Yang, Ling; Xu, Zhenbo
ABSTRACT: Since antimicrobial resistance, especially β-lactam resistance genes were common in clinical Escherichia coli strains, this study had designed and developed multiplex amplification platform for rapid and accurate detection of such resistance genes in 542 clinical E. coli isolates. The obtained specimens were subjected to bacteriological examination, antimicrobial susceptibility testing, and detection of β-lactamase genes and plasmid replicons. The major virulence genes were detected by 7 groups of multiplex PCR and eight groups of multiplex PCR were designed to detect 8 different plasmid replicons including parA-parB, iteron, repA, and RNAI . It was found that most MDR isolates were co-resistant to penicillins (AMP) and fluoroquindones (LVX, CIP) and distribution of LVX and CIP resistance was significantly higher among female than male gender. RNAI (AY234375) showed the highest detection rate, followed by the iteron (J01724) and repA (M26308), indicating the relatively higher carriage rate of corresponding plasmids. Bla OXA acquired the highest carriage rate, followed by group 2 bla CTX-M and bla SHV-1, indicating their prevalence among clinical E. coli . Among the β-lactamase genes, bla OXA acquired the highest carriage rate, followed by group 2 bla CTX-M and bla SHV-1, indicating their prevalence among clinical E. coli . The RNAI (AY234375) showed the highest detection rate, followed by the iteron (J01724) and repA (M26308), indicating the relatively higher carriage rate of the corresponding plasmids by clinical E. coli isolates. It is shown that the developed multiplex amplification methodology is applicable to AMR detection, and such identification of plasmid replicons and β-lactamase genes may aid in the understanding of clinical E. coli isolate epidemiology. Graphical Abstract: uf0001